Evolution of complexity and natural selection: suture complexity and its relation to taxonomic longevity in Cretaceous ammonoids - Pérez-Claros, Juan Antonio; Bengtson, Peter (Cretaceous research, 2017)
A sample of 682 suture lines belonging to 204 Cretaceous planispiral ammonoid genera shows a positive, significant relationship between suture complexity (measured as fractal dimension [Df]) and generic longevity. However, during the Cretaceous there was no increase in the mean fractal dimension. This paradox is due to the evolutionary dynamic during this time span comprising mainly the appearance, disappearance (or anagenetic transformation) of those genera with simpler sutures and, consequently, the maximal values of fractal dimension were more stable in time. These results contrast with (i) the hypothesis that simple morphologies are linked to low ecological specialization and (ii) the idea that the role of natural selection can be unambiguously deduced from stratigraphic ranges.
Gesehen am 28.05.2020
Available online: 9 February 2017